Spatially Restricted G Protein-coupled Receptor Activity via Divergent Endocytic Compartments - Jean-Alphonse, Frederic (American Society for Biochemistry and Molecular Biology, 2014)

(untitled)
Postendocytic sorting of G protein-coupled receptors (GPCRs) is driven by their interactions between highly diverse receptor sequence motifs with their interacting proteins, such as postsynaptic density protein (PSD95), Drosophila disc large tumor suppressor (Dlg1), zonula occludens-1 protein (zo-1) (PDZ) domain proteins. However, whether these diverse interactions provide an underlying functional specificity, in addition to driving sorting, is unknown. Here we identify GPCRs that recycle via distinct PDZ ligand/PDZ protein pairs that exploit their recycling machinery primarily for targeted endosomal localization and signaling specificity. The luteinizing hormone receptor (LHR) and β2-adrenergic receptor (B2AR), two GPCRs sorted to the regulated recycling pathway, underwent divergent trafficking to distinct endosomal compartments. Unlike B2AR, which traffics to early endosomes (EE), LHR internalizes to distinct pre-early endosomes (pre-EEs) for its recycling. Pre-EE localization required interactions of the LHR C-terminal tail with the PDZ protein GAIP-interacting protein C terminus, inhibiting its traffic to EEs. Rerouting the LHR to EEs, or EE-localized GPCRs to pre-EEs, spatially reprograms MAPK signaling. Furthermore, LHR-mediated activation of MAPK signaling requires internalization and is maintained upon loss of the EE compartment. We propose that combinatorial specificity between GPCR sorting sequences and interacting proteins dictates an unprecedented spatiotemporal control in GPCR signal activity.